DISRUPTIVE HUMOUR: A CITIZEN PERSPECTIVE IN SOCIAL MEDIA IMAGES FROM MASS PROTESTS - Neumayer, Christina; Rossi, Luca; Jensen, Minna S. (AoIR Selected Papers of Internet Research, 2020)
In this research we ask which role humorous social media images play for the representation of political protest in social media. To do so, we collected tweets (n=678946) based on protest hashtags from the G20 protests in Hamburg July 6-8 2017. With a social network analysis we find that while we can see clusters around user accounts of activist collectives, media institutions, and authorities (such as the Hamburg police), we cannot observe a network centred around user accounts of residents of Hamburg. As seemingly neutral humorous perspectives which do neither take the side of the activists or the authorities, these images seem to be shared across various clusters in the network. Yet, these are among the most frequently shared tweets based on number of retweets and mentions. Through a narrative analysis of the most frequently shared tweets with a particular focus on such humorous juxtapositions of the protests and the everyday life of residents, we find that these seemingly apolitical images and videos shared across communities, still play a disruptive role in the narrative about political protest. We argue that the privileging of humorous content that users are perhaps more inclined to share in social media than political messages, activists’ grievances or violent imagery, might (while not actively taking sides) push activists’ grievances in the background and make their actions appear as disruptive. With these findings, this research contributes to furthering our understanding of how the logics of social media might influence narratives of contemporary protests.